Architecture of a cyberphysical avatar - Han, Song; Mok, Aloysius K.; Meng, Jianyong; Wei, Yi-Hung; Huang, Pei-Chi; Leng, Quan; Zhu, Xiuming; Sentis, Luis; Kim, Kwan Suk; Miikkulainen, Risto (Proceedings of the ACM/IEEE 4th International Conference on Cyber-Physical Systems, 2013)
This paper introduces the concept of a cyberphysical avatar which is defined to be a semi-autonomous robotic system that adjusts to an unstructured environment and performs physical tasks subject to critical timing constraints while under human supervision. Cyberphysical avatar integrates the recent advance in three technologies: body-compliant control in robotics, neuroevolution in machine learning and QoS guarantees in real-time communication. Body-compliant control is essential for operator safety since cyberphysical avatars perform cooperative tasks in close proximity to humans. Neuroevolution technique is essential for "programming" cyberphysical avatars inasmuch as they are to be used by non-experts for a large array of tasks, some unforeseen, in an unstructured environment. QoS-guaranteed real-time communication is essential to provide predictable, bounded-time response in human-avatar interaction. By integrating these technologies, we have built a prototype cyberphysical avatar testbed.